2010
DOI: 10.1142/s0218195910003232
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Watchman Route Problem With Discrete View Cost

Abstract: In this paper, we introduce a generalized version of the Watchman Route Problem (WRP) where the objective is to plan a continuous closed route in a polygon (possibly with holes) and a set of discrete viewpoints on the planned route such that every point on the polygon boundary is visible from at least one viewpoint. The total cost to minimize is a weighted sum of the view cost, proportional to the number of viewpoints, and the travel cost, the total length of the route. We call this problem the Watchman Route … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The cost of a path can be modeled as the weighted sum of the length of the path (travel time) and the number of measurements along the path (measurement time). Wang et al [15] first introduced this objective function for WRP for the case of a single robot and termed it the Generalized WRP (GWRP). They showed that GWRP is NP-hard and presented a O(polylog n) approximation for the restricted case when each viewpoint is required to see a complete polygon edge.…”
Section: Kumar@seasupennedumentioning
confidence: 99%
“…The cost of a path can be modeled as the weighted sum of the length of the path (travel time) and the number of measurements along the path (measurement time). Wang et al [15] first introduced this objective function for WRP for the case of a single robot and termed it the Generalized WRP (GWRP). They showed that GWRP is NP-hard and presented a O(polylog n) approximation for the restricted case when each viewpoint is required to see a complete polygon edge.…”
Section: Kumar@seasupennedumentioning
confidence: 99%
“…Although feasible solutions are of value, an optimal solution is desirable both to permit a shorter-duration inspection and to improve the ease of implementation on a field robotic system. Unfortunately, even in simple cases the coverage path planning problem is equivalent to NP-hard variants of the watchman route problem (Chin and Ntafos, 1988;Wang et al, 2010), and geometric path planning over obstacles is PSPACE-hard in general (Reif, 1979), so we do not seek a globally optimal solution. We propose an iterative improvement procedure which, given a feasible, fullcoverage inspection tour as input, gradually shortens the tour and reduces the number of view configurations, making progress toward a locally optimal solution.…”
Section: Introductionmentioning
confidence: 99%
“…The problems related to travelling route problems of mobile robots are handled in [8] and [9]. They consider that a travelling route is generated by travelling salesman problem (TSP) based method which connects fixed camera locations to cover all regions.…”
Section: Introductionmentioning
confidence: 99%